Harmonization of Knowledge Representation: Integrating Systems Thinking Ideas with Appropiate Domain Representation Strategies - Olmos Sanchez, Karla Miroslava (2024)
The cognitive era is marked by the prevalence of Artificial Intelligence and information technologies, which implies digital transformation. However, the swift changes and oversimplified synthesis applied to complex domains have resulted in inadequate transformations, particularly in addressing intricate contexts. This paper examines the need for a methodological framework to guide the conceptualization and development of smart solutions. Moreover, the paper underscores the need to establish a comprehensive framework combining Knowledge Management and Systems Thinking to tackle complex situations effectively. It accentuates the significance of comprehending diverse perspectives, exploring solutions alternatives, and managing tacit knowledge within rapidly evolving domains. The integration of Knowledge Management and Systems Thinking through the KMoS-SSA framework allows the difficulty of complex domains to be effectively addressed, facilitating the conceptualization and development of intelligent solutions that are feasible, effective and desirable.